2023
DOI: 10.1039/d3su00193h
|View full text |Cite
|
Sign up to set email alerts
|

The heat-promoted metal–support interaction of a PtCu/SiO2 carbon-free catalyst for the methanol oxidation and oxygen reduction reactions

Quanqing Zhao,
Han Zhi,
Liu Yang
et al.

Abstract: Pt shows excellent catalytic activity towards the methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR), but suffers from deactivation due to the weak interaction with the carbon support and the oxidation of carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The electrical conductivity of PtNi/SiO 2 was determined to be 1.56 mS cm –1 , as illustrated in Figure S2. Furthermore, it has been shown that metal oxide/doped-metal oxides, exhibiting reduced electronic conductivity, exhibit enhanced ORR activity in contrast to Pt supported over carbon. , For Pt/C, the observed conductivity was 10.3 mS cm –1 , which is higher compared to PtNi/SiO 2 . This discrepancy arises due to the interconnected nature of carbon particles in Pt/C, facilitating electronic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity of PtNi/SiO 2 was determined to be 1.56 mS cm –1 , as illustrated in Figure S2. Furthermore, it has been shown that metal oxide/doped-metal oxides, exhibiting reduced electronic conductivity, exhibit enhanced ORR activity in contrast to Pt supported over carbon. , For Pt/C, the observed conductivity was 10.3 mS cm –1 , which is higher compared to PtNi/SiO 2 . This discrepancy arises due to the interconnected nature of carbon particles in Pt/C, facilitating electronic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…SiO 2 was also developed as a support for the PtCu catalyst [62] by Zhao's group. TEM images of PtCu/SiO 2 -40% revealed that the metal nanoparticles were closely attached to the SiO 2 nanospheres, indicating a strong interaction between PtCu alloy and SiO 2 nanospheres, which is demonstrated in Figure 2b.…”
Section: Metal Oxide Support Modificationmentioning
confidence: 99%
“…SiO 2 [62] CuSiO 3 [63] TiO 2−x N [12] Pr 0.15 Ce 0.85 O 2 [64] Reactant Selection and Synthesis Strategies…”
mentioning
confidence: 99%